Strategi Optimalisasi Administrasi Sekolah dalam Meningkatkan Mutu Layanan Pendidikan di UPTD SMPN 2 Parepare - Anatasia B (Education Management: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyse strategies for optimising school administration in order to improve the quality of educational services. The research method employed is a descriptive qualitative approach using a case study methodology, which is suitable for exploring administrative practices and strategies in depth. The strategies analysed include human resource recruitment and training, the digitisation of administration, headteacher leadership, and workload evaluation. The results of the study indicate that the implementation of these strategies can improve the management of archives and documents, expedite administrative services for teachers, students, parents, and stakeholders, and enhance the satisfaction of all parties. School administration optimisation not only streamlines operations but also directly contributes to improving the quality of education and the school’s competitiveness.